The Place of Studio - David Cronrath (Oz, 1997)
Placing the studio within most curricula of architecture is not a particularly difficult locational task for most professionals, educators, or students. It stands in a central position. This position is held by the studio whether it is seen as the point toward which other information and activities flow (similar to the undergraduate natural science laboratory), or the point from which other activities and courses extend out (as in the American Beaux-Arts), or finally a combination of both, an ebb and flow, to and from. Ed.note: An article about studio pedagogy by a University of Nebraska faculty member who uses his students’ projects as examples.